Pengaruh Entrepreneurial Knowledge, Self Efficacy Dan Locus Of Control Terhadap Intensi Berwirausaha Pada Mahasiswa Program Studi Manajemen Universitas Muhammadiyah Sidoarjo - Astutik, Rohma Puji; Abadiyah, Rifdah; Andriani, Dewi (Universitas Islam Kadiri, 2025)
This study aims to determine the effect of Entrepreneurial Knowledge, Self Efficacy and Locus of Control on Entrepreneurial Intentions in Management Study Program Students at Muhammadiyah University of Sidoarjo. Analysis of Entrepreneurial Knowledge, self-efficacy, and locus of control on entrepreneurial intensity, it can be concluded that Entrepreneurial Knowledge has a significant effect on entrepreneurial intention of management study program students at Muhammadiyah University of Sidoarjo, with the results that the higher the knowledge possessed, the higher the intensity of students to become entrepreneurs. This study uses a quantitative method of descriptive research with a population of management students at Muhammadiyah University of Sidoarjo who have taken the entrepreneurship journey course. The sampling technique uses a non-probability sampling method with purposive sampling involving 196 respondents. This study uses data collection techniques using the help of statistical tests Statistical Package for the Social Sciences (SPSS version 25) to test the hypothesis. The results of this study indicate that Entrepreneurial Knowledge self Efficacy, Locus Of Control, there is a significant influence on the Entrepreneurial Intention of management students of Muhammadiyah University of Sidoarjo.